Elinogrel: pharmacological principles, preclinical and early phase clinical testing. (July 2010) - Ueno, Masafumi; Rao, Sunil V; Angiolillo, Dominick J
Antiplatelet drug therapy represents the cornerstone of treatment for cardiovascular atherothrombotic disease processes. Dual antiplatelet therapy with aspirin and oral ADP-receptor antagonists such as clopidogrel are currently the standard care for prevention of ischemic events in patients with acute coronary syndrome and who are undergoing percutaneous coronary intervention. However, despite the clinical benefit associated with clopidogrel therapy, this drug has several limitations, including a broad interindividual response variability, drug–drug interactions, slow onset of action and irreversible platelet inhibition, emphasizing the need for novel P2Y12 -receptor antagonists. Elinogrel (PRT060128) is a reversible, potent and competitive inhibitor of the P2Y12 receptor with a fast onset and offset of action that can be administered by both oral and intravenous routes and rapidly achieves near complete platelet inhibition. Preclinical and early-phase clinical testing have shown promising results with this novel compound, which awaits further testing in outcome-driven clinical trials. This article provides an overview of the current level of knowledge regarding elinogrel, focusing on its pharmacologic properties and preclinical and early-phase clinical development.